2016
DOI: 10.1002/adsc.201600412
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Control in the Gold(I)‐Catalyzed Cyclization of βPropargylamino Acrylic Esters and Further Transformations of the Resultant Dihydropyridines

Abstract: N-Protected b-propargylamino acrylic estersw ith ap ush-pull olefinic bonda ffordedg ood to high yields of dihydropyridines upont reatment with 5% tris(2-furyl)phosphine-gold(I) chloride/silver(I) tetrafluoroborate [(TFP)AuCl/AgBF 4 ]i na nhydrousb enzene.C arbamate and sulfonyl groups were employed for nitrogen protection. On am odel enyne, the p-methoxybenzenesulfonyl (MBS) group was found to be ab etter protective group than tosyl in termso fc yclization yield, and also the yield of elimination to the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To further demonstrate the versatility of this one-pot sequential reaction, the scope for 2,3,4-trisubstituted pyridines was investigated (Scheme ). This substitution pattern is generally accessed via ring substitution reactions by sequential cross-couplings as there are few synthetic routes available. With our one-pot protocol, 2,3,4-trisubstituted pyridine derivatives were obtained by using N -triphenylsilylamine, internal alkynes, and 3-substituted α,β-unsaturated aldehydes, which were either commercially available or readily synthesized using a Wittig reaction. A variety of internal alkynes were screened for altering the substituents at 2- and 3-positions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further demonstrate the versatility of this one-pot sequential reaction, the scope for 2,3,4-trisubstituted pyridines was investigated (Scheme ). This substitution pattern is generally accessed via ring substitution reactions by sequential cross-couplings as there are few synthetic routes available. With our one-pot protocol, 2,3,4-trisubstituted pyridine derivatives were obtained by using N -triphenylsilylamine, internal alkynes, and 3-substituted α,β-unsaturated aldehydes, which were either commercially available or readily synthesized using a Wittig reaction. A variety of internal alkynes were screened for altering the substituents at 2- and 3-positions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in the synthesis of multisubstituted pyridines include transition metal-catalyzed intermolecular cyclization to access functionalized pyridine derivatives from pre-functionalized substrates. ,,, A variety of intermolecular cyclization methodologies have been developed to access tri-substituted pyridines, including [2+2+2], [2+2+1+1], [3+3], [3+2+1], and [4+2] cycloadditions and cycloisomerizations. ,,, A majority of the reported methodologies focus on the synthesis of 2,3,6-, 2,3,5-, and 2,4,6-trisubstituted pyridines with fewer methodologies focusing on 2,3,4- and 2,4,5-trisubstituted pyridines (Scheme ). ,, Only a limited number of synthetic strategies are available to access 3,4,5-trisubstituted pyridines, making it a challenging substitution pattern, which is generally accessed with sequential cross-coupling reactions. , Diverse tri-substitution patterns of pyridines are found in a number of FDA-approved drugs such as etoricoxib (2,3,5-), lansoprazole (2,3,4-), and netupitant (2,4,5-) (Figure ). The development of a new, facile strategy to access the less explored pyridine substitution patterns from readily available substrates may enable the development of alternatively substituted pyridines for exploration in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of 4a was confirmed by comparison of its NMR spectrum with previously reported data ( Table S1 ) (Hellal et al, 2008 ). Recently, many research groups have continuously reported the efficiency of various transition-metal Lewis acid catalysts for alkyne activation in cycloisomerization reaction (Abbiati et al, 2003 ; Yan et al, 2007 ; Cacchi et al, 2008 ; Saito et al, 2009 ; Jiang et al, 2010 ; Fei et al, 2011 ; Mikušek et al, 2016 ; Vessally et al, 2016 ; Nizami and Hua, 2017 ; Sakthivel et al, 2017 ; Gianni et al, 2018 ; Lyubov'N et al, 2018 ; Mancuso et al, 2018 ; Ahn et al, 2019 ). To increase the product yield, cycloisomerization was performed in the presence of various metal catalysts, including Ag(I), Au(I), Cu(I), Cu(II), and In(III).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, intensive efforts to establish efficient synthetic methods for pyridine-fused coumarins and natural products using the metal-catalyzed cycloisomerization of N-propargyl enaminone intermediates have been reported (Ahn et al, 2019;Yoon and Han, 2019). In these studies, the pyridine moiety was constructed in a highly 6-endo-selective manner, which can be explained by σ-bond formation between the nucleophilic enolizable αposition and exo-position of the electrophilic alkyne-metal complex and subsequent spontaneous oxidation to form a stable aromatic pyridine ring (Abbiati et al, 2003;Yan et al, 2007;Cacchi et al, 2008;Jiang et al, 2010;Fei et al, 2011;Mikušek et al, 2016;Lyubov'N et al, 2018;Ahn et al, 2019). It was anticipated that construction of the pyridine moiety via cycloisomerization of N-propargylamine intermediates in the last-stage would be an efficient strategy for the synthesis of 3aryl-5-azaisocoumarins.…”
Section: Introductionmentioning
confidence: 99%
“…The heterocycle benzoxazepines are privileged scaffolds in natural biologically products [ 1 , 2 , 3 , 4 ], pharmaceutical chemistry [ 5 , 6 ] and functionalized materials [ 7 , 8 , 9 , 10 ]. As such, Sintamilv ( I ) is an efficient antidepressant [ 11 ]; H1 receptor antagonist ( II ) is a selective antihistaminic agent [ 12 ]; and Sintamil ( III ) is a benzoxazepine analogue ( Scheme 1 ) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%